Synthesis, characterization, and biological evaluation of new oxime-phosphazenes - Koran, Kenan; Özkaya, Ahmet; Özen, Furkan; Çil, Erol; Arslan, Mustafa (My University, 2013)
Hexachlorocylotriphosphazene (1) was reacted with 4-hydroxy-3-methoxybenzaldehyde to give hexakis[(4-formyl-2-methoxy)phenoxy]cyclotriphosphazene (2). Hexakis[(4-(hydroxyimino)2-methoxy)phenoxy]cyclotriphosphazene (3) was synthesized by reaction of 2 with hydroxlamine hydrochloride in pyridine. Compound 3 was reacted with benzyl chloride, acetyl chloride, allyl bromide, benzoyl chloride, propanoyl chloride, 4-methoxybenzoyl chloride, 2-chlorobenzoyl chloride, chloroacetyl chloride, methyl iodide, and thiophene-2-carbonyl chloride. From these reactions, full or partially substituted compounds were obtained, usually in high yields. Pure or defined products could not be obtained from reaction of 3 with methacryloyl chloride and O-acetylsalicyloyl chloride. The structures of the compounds were determined by elemental analysis, and IR, 1H, 13C, and 31P NMR spectroscopy. The synthesized compounds were screened for in-vitro antimicrobial activity against two Gram-positive bacteria (Staphylococcus aureus and Enterococcus faecalis), two gram-negative bacteria (Escherichia coli and Klebsiella pneumonia), and fungal strains (Aspergillus niger, and Candida albicans) by the agar well diffusion method. Few compounds had significant activity against both Gram-positive and Gram-negative bacteria. None of the compounds had antifungal activity except compounds 7 and 9, which had moderate activity.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Hexachlorocyclotriphosphazene; Phosphazene; Oxime-phosphazenes; Antibacterial; Antifungal